2021
DOI: 10.18203/2394-6040.ijcmph20214278
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude towards organ donation: a study among medical and nursing students of a medical college

Abstract: Background: Organ transplantation is one such field of modern medical sciences which has progressed over the years and has given hope for those suffering with end stage organ diseases. There are lot of advancement in technology to preserve and transplant of organs but with this technological advancement also there are still gaps in awareness regarding the subjects. To find the gaps this study was carried out in medical college students.Methods: A cross-sectional analytical study was conducted in medical colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The interpretation of this result from the researcher’s point of view is that the students in the fourth year had more years of learning, so they had knowledge about the donation. These findings are in accordance with many previous studies obtained from[ 20 21 22 23 24 25 26 27 ], who reported that the studies demonstrated the final-stage nursing students had more knowledge from other stages.…”
Section: Discussionsupporting
confidence: 93%
“…The interpretation of this result from the researcher’s point of view is that the students in the fourth year had more years of learning, so they had knowledge about the donation. These findings are in accordance with many previous studies obtained from[ 20 21 22 23 24 25 26 27 ], who reported that the studies demonstrated the final-stage nursing students had more knowledge from other stages.…”
Section: Discussionsupporting
confidence: 93%
“…Intoday's time the most preferred mode for the treatment for end-stage organ disease and organ failures is organ transplantation [1]. Transplantation is the moving of an organ from one body to another or from a donor site on the patient's own body, for the purpose of replacing the recipient's damaged or absent organ [2].Common transplantations include kidney, heart, liver, pancreas, intestines, lungs, bones, bone marrow, skin, and cornea [3]. Significant shortage of organs in India is a major concern, majority of organ failure patients die while on the waiting list due to the lack of timely availability of organs.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the organ transplant system is at the intersection of various disciplines, such as public health, logistics and information systems, this area has largely been neglected in mainstream supply chain management research. In contrast, it is generally assigned to disciplines with a solid clinical/medical science emphasis (Arshad et al , 2019; Ghose et al , 2021). Therefore, this study contributes to the supply chain management literature by creating a hierarchical model to reveal the complex interdependencies between organ transplant supply chain challenges with theoretically grounded explanations.…”
Section: Introductionmentioning
confidence: 99%